Poverty and Public Policy: Local Government Efforts to Reduce Extreme Poverty - Widodo, Suranto Eko; Wulandari, Ratna (Department of Government Studies, Universitas Muhammadiyah Buton., 2024)
This study investigates the local government's endeavors in combating extreme poverty within the context of Poverty and Public Policy. Through a comprehensive analysis of local government initiatives, methodologies, and outcomes, this research aims to provide insights into effective strategies for poverty reduction at the grassroots level. Utilizing a mixed-methods approach, including qualitative interviews, policy analysis, and statistical modeling, the study examines the efficacy of various poverty alleviation programs implemented by local governments. Findings from this research highlight the significance of coordinated efforts between local governments, community stakeholders, and non-governmental organizations (NGOs) in addressing extreme poverty. Moreover, the study underscores the importance of context-specific interventions tailored to the unique socio-economic landscape of each locality. Recommendations include the enhancement of community participation in policy formulation, the implementation of targeted poverty reduction programs, and the provision of comprehensive social assistance schemes. This research contributes to the body of knowledge on poverty alleviation by shedding light on the role of local governments in addressing extreme poverty. By elucidating effective strategies and policy frameworks, this study aims to inform policymakers, practitioners, and scholars alike, thus facilitating evidence-based decision-making and fostering sustainable poverty reduction efforts.